(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Letters are the oldest means of communication and as such, the technique is used in literature also. Letters carry an emotional significance and are important social convention. When we study the narrative technique in literature, it is called Epistolary Technique. Epistolary novels have the narrative technique wherein the writers use the medium of letters, diary entries, and other written documents,